INNOVATION OF VIRTUAL REALITY TEACHING MEDIA IN CIVIC EDUCATION LEARNING IN THE ERA OF TECHNOLOGICAL DISRUPTIONS: A LITERATURE REVIEW OF CIVIC KNOWLEDGE TRANSFORMATION - Latifatus Sariroh; Siti Awaliyah; Sri Untari (Universitas Negeri Medan, 2026)
Technological advancements in the era of disruption require a shift toward more interactive learning, including in Pancasila and Civic Education (PPKn). However, conventional teaching practices often result in low student engagement and limited civic knowledge understanding. This study aims to analyze the use of Virtual Reality (VR) as a learning medium, examine its effectiveness in transforming civic knowledge, and identify its advantages, limitations, and implications. The research employs a literature review method by analyzing relevant scientific sources published within the last 5–10 years through selection and synthesis processes. The findings indicate that VR possesses immersive, interactive, and multisensory characteristics that enhance student engagement, conceptual understanding, critical thinking, and social awareness. These findings are supported by studies showing that VR improves engagement and meaningful learning experiences . However, its implementation faces challenges such as high costs, infrastructure limitations, and user readiness. The contribution of this study lies in providing a comprehensive analysis that integrates technological, pedagogical, and civic perspectives, while strengthening the discourse on civic knowledge transformation in PPKn learning. Therefore, VR has strong potential as an innovative learning medium to improve civic education quality.. Key words: Virtual Reality, Civic Knowledge, Civic Education